Pro-ecological hotel policies as assessed by guests - Kapera, Izabela; Wszendybył-Skulska, Ewa (Turyzm/Tourism, 2017)
The purpose of the research was to learn whether pro-ecological policies are important to guests staying at hotels. It is based on a survey of 274 guests staying at 23 hotels in Poland. Research has shown that 32.1% of survey participants consider proecological issues when choosing a stay at a hotel. Close to 62% of guests believe that hotels should pursue such initiatives which are believed to yield environmental benefits, reductions in hotel operating costs, promotional effects, and a positive impact on a hotel's image. More than 35% of guests would be willing to pay more for a stay at a hotel that pursues environmentally-friendly policies. It is important to emphasize that pro-ecological activity is not used in hotel rankings in Poland.